Hypertropic Osteopathy (Marie Diseases) in The German Shepherd Dog - Dhirgo Adji (Jurnal Sain Veteriner, 2013)
Abstract A Male German Shepherd dog, five years old, twenty six kg of body weight was submitted to Professor Soeparwi Animal Hospital, Faculty of Veterinary Medicine, Gadjah Mada University by Mr. Siswo Han, the owner who lives in Cangkringan, Yogyakarta on May 13, 2013. The dog was suffered from the pain and lameness on the front-left extremity for about 2 weeks. The dog having registered number of 8738/V/A/RSH/13 did not show any specific clinical signs, except the lameness. Skin and hairs, mucous membranes, lymphoid glands, and respiratory, digestive, circulatory and uropoetica organs as well were within the normal limits. The result of standard blood test for both red blood cell and white blood cell were still within normal values. Evaluation of fecal sample of the dog was also normal meaning that no parasites were found in the fecal sample. Radiographic analysis of the upper left extremity and the lungs area showed that there was an irregular bone growth on the left caput humeri, and the lungs were normal. Based on the lesion, the dog was diagnosed as having a hyperthropic osteopathy (Marie Disease).